Association of Single-Nucleotide Polymorphisms in Monoubiquitinated FANCD2-DNA Damage Repair Pathway Genes With Breast Cancer in the Chinese Population. (24th December 2018) - Chen, Fei-Yu; Wang, Hao; Li, Hui; Hu, Xue-Li; Dai, Xu; Wang, Shou-Man; Yan, Guo-Jiao; Jiang, Ping-Lan; Hu, Yuan-Ping; Huang, Juan; Tang, Li-Li
Objective: The aim of the study was to estimate breast cancer risk conferred by individual single-nucleotide polymorphisms of breast cancer susceptibility genes. Methods: We analyzed the 48 tagging single-nucleotide polymorphisms of 8 breast cancer susceptibility genes involved in the monoubiquitinated FANCD2–DNA damage repair pathway in 734 Chinese women with breast cancer and 672 age-matched healthy controls. Results: Forty-five tagging single-nucleotide polymorphisms were successfully genotyped by SNPscan, and the call rates for each tagging single-nucleotide polymorphisms were above 98.9%. We found that 13 tagging single-nucleotide polymorphisms of 5 genes ( Parter and localizer of Breast cancer gene2 ( PALB2), Tumour protein 53 ( TP53), Nijmegen breakage syndrome 1, Phosphatase and tensin homolog deleted from chromosome 10 ( PTEN), and Breast cancer gene 1 ( BRCA1-interacting protein 1) ) were significantly associated with breast cancer risk. A total of 5 tagging single-nucleotide polymorphisms (rs2299941 of PTEN, rs2735385, rs6999227, rs1805812, and rs1061302 of Nijmegen breakage syndrome 1 ) were tightly associated with breast cancer risk in sporadic cases, and 5 other tagging single-nucleotide polymorphisms (rs1042522 of TP53, rs2735343 of PTEN, rs7220719, rs16945628, and rs11871753 of BRCA1-interacting protein 1 ) were tightly associated with breast cancer risk in familial and early-onset cases. Conclusions: Some of the tagging single-nucleotide polymorphisms of 5 genes ( PALB2, TP53, Nijmegen breakage syndrome 1, PTEN, and BRCA1-interacting protein 1 ) involved in the monoubiquitinated FANCD2–DNA damage repair pathway were significantly associated with breast cancer risk.